Evolving Paradigms: The Translation of Zhuang Medical Terminology through the Lens of Cultural Translation - Liao, Wenqi (Pacific International Journal, 2025)
This study systematically investigates the English translation of terminology, texts, and cultural concepts in Guangxi Zhuang medicine, revealing critical issues in current practices such as terminological inconsistency, mistranslation of culture-specific terms, overreliance on transliteration, and inappropriate adoption of Western medical terminology. Through qualitative analysis based on a self-built Zhuang-Chinese-English parallel corpus, the study proposes an integrated application of diversified strategies—including transliteration with annotation, free translation, and calque—to establish a systematic translation framework. It emphasizes that translating Zhuang medicine is a cross-cultural practice integrating medical, linguistic, and ethnic cultural knowledge. The findings offer theoretical and practical references for the international translation of traditional Chinese medicine and other ethnic medical systems.